Penerapan Model Pembelajaran Predict Observe Explain untuk Meningkatkan Keterampilan Pemecahan Masalah Kelas IV SDIT Asy-Syifa Kota Jambi - Reza Saprita Yuanda; Ika Aryastuti Hasanah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the low problem solving skills of students in Natural and Social Sciences subjects. The purpose of this study was to determine the improvement of students' problem solving skills in Natural and Social Sciences subjects through the application of the Predict Observe Explain learning model. Researchers used a class action research method with the research subjects, namely the fourth grade homeroom teacher and 23 fourth grade students. Research activities were carried out for two cycles and each cycle consisted of two meetings. Data collection techniques using observation techniques, tests, interviews and documentation. While data analysis techniques using qualitative and quantitative data analysis. Based on the results of the study, it shows that the application of the Predict Observe Explain learning model can improve problem solving skills. This improvement can be seen in the activities that have been carried out for two cycles, namely the action in cycle I, the average student problem solving skills increased to 53.71% in the moderate / sufficient category. Then in cycle II, the average student problem solving skills increased to 77.21% in the high / good category. It can be concluded that through the application of the Predict Observe Explain learning model in Natural and Social Sciences subjects can improve the problem solving skills of fourth grade students of Asy-Syifa Integrated Islamic Elementary School Jambi City.